Performance comparison of seed generation techniques of stimulated Brillouin scattering-based microwave photonics amplifier and filter - Abbas, Shahad Khudhair; Cholan, Noran Azizan; Zan, Mohd Saiful Dzulkefly; Mahdi, Mohd Adzir; Mokhtar, Makhfudzah; Zan, Zuraidah (Universiti Putra Malaysia Press, 2024)
This work presents a Brillouin amplification performance comparison of seed generation techniques using double-sideband suppressed carrier (DSB-SC) and single-sideband suppressed carrier (SSB-SC) modulations. The SSB-SC is obtained using an optical bandpass filter (OBPF) and in-phase and quadrature Mach-Zehnder modulator (IQ-MZM). All three techniques provide high amplification performance with optical signal-to-noise ratio (OSNR) enhancement of 37.47 dB, 33.14 dB, and 32.67 dB using DSB-SC, SSB-SC/OBPF, and SSB-SC/IQ-MZM, respectively. The best seed generation technique is using the DSB with a signal amplification of 62.47 dB. The technique presents ~4 dB higher OSNR enhancement due to the dual-energy transfer obtained from the beating process of the DSB than SSB. A ~3 dB OSNR reduction is found when pump linewidth (LW) was changed from 1kHz to 50 MHz, which suggests using a low-cost pump source whenever the OSNR reduction is not critical. The work also shows that the three techniques required 10 dBm stimulated Brillouin scattering threshold (SBST) to stimulate the process. An additional analysis of DSB-SC shows that a high-carrier suppression during the seed generation technique using MZMs is insignificant to the amplification performance. The high-carrier suppression produces a high seed signal power that distorts the Brillouin gain spectrum (BGS) and the pump depletion region, hence reducing the Brillouin gain (BG). Since carrier suppression is not a primary consideration, a cost-effective MZM with a modest extinction ratio requirement is allowed. The relaxed requirement of the pump’s linewidth and MZM’s extinction ratio suggest a cost-effective development of the SBS-based optical amplifier with narrow filter bandwidth.